Effect of Organic Loading Rate and Temperature on the Anaerobic Digestion of Municipal Solid Waste: Process Performance and Energy Recovery - Jiang, Junfeng; He, Shuibin; Kang, Xihui; Sun, Yongming; Yuan, Zhenhong; Xing, Tao; Guo, Yufang; Li, Lianhua (Frontiers in Energy Research, 2020)
This study investigated the effects of organic loading rates (OLRs) and temperature on the performance and stability of anaerobic digestion treating the organic fraction of municipal solid waste (OFMSW) in a semi-continuous mode. Furthermore, a preliminary energy analysis was conducted to determine the optimal application parameters for anaerobic digestion of OFMSW. Results showed that the maximum achievable OLR was 9.00 g VS/(L·d), with a volumetric biogas yield of 4.03 L/(Ld) and 4.31 L/(Ld) for mesophilic and thermophilic systems, respectively. However, the preliminary energy analysis showed higher energy conversion efficiency was achieved for the system operated at an OLR of 7.50 g VS/(L·d). The system operated at the thermophilic condition had a higher total energy due to more electricity and heat energy generated than the mesophilic one. Therefore, the recommended operating conditions for the anaerobic digestion of OFMSW is an OLR of 7.50 g VS/(L·d) and thermophilic condition. Based on the annual yield of OFMSW in China, the estimated net output energy was 69970.61 GWh per year.